Consumption of diets with low advanced glycation end products improves cardiometabolic parameters: meta-analysis of randomised controlled trials - Estifanos Baye (Nature Portfolio, 2017)
Abstract Studies examining the effects of consumption of diets low in advanced glycation end products (AGEs) on cardiometabolic parameters are conflicting. Hence, we performed a meta-analysis to determine the effect of low AGE diets in reducing cardiometabolic risk factors. Seventeen randomised controlled trials comprising 560 participants were included. Meta-analyses using random effects models were used to analyse the data. Low AGE diets decreased insulin resistance (mean difference [MD] −1.3, 95% CI −2.3, −0.2), total cholesterol (MD −8.5 mg/dl, 95% CI −9.5, −7.4) and low-density lipoprotein (MD −2.4 mg/dl, 95% CI −3.4, −1.3). There were no changes in weight, fasting glucose, 2-h glucose and insulin, haemoglobin A1c, high-density lipoprotein or blood pressure. In a subgroup of patients with type 2 diabetes, a decrease in fasting insulin (MD −7 µU/ml, 95% CI −11.5, −2.5) was observed. Tumour necrosis factor α, vascular cell adhesion molecule-1, 8-isoprostane, leptin, circulating AGEs and receptor for AGEs were reduced after consumption of low AGE diets with increased adiponectin and sirtuin-1. Our findings suggest that diets low in AGEs may be an effective strategy ﻿for﻿ improving cardiometabolic profiles in individuals with and without type 2 diabetes.